Arthroplasty or Arthrodesis in the CJR Era: Medical Resource Utilization for Patients with Ankle Arthritis. Issue 3 (14th September 2018) - Hogan, MaCalus; Chambers, Monique; Kromka, Joseph; Carney, Dwayne; Yan, Alan; Porter, Jake
Category: Ankle Arthritis Introduction/Purpose: Ankle arthritis can be a debilitating disease that results in decreased daily activity and chronic morbidity. Many patients elect for surgical intervention to minimize pain and improve function. To curb costs associated with the increasing demand for total joint arthroplasty (TJA) in the growing elderly Medicare population, CMS announced the Comprehensive Care for Joint Replacement (CJR) model, which included total ankle arthroplasty. To provide continued quality care and cost containment, it is necessary to determine the optimal surgical intervention for patients that could fall within the CJR program. Therefore, we sought to determine the impact of surgical fixation on functional outcomes, systemic utilization, and medical expenditures for patients with ankle arthritis. Methods: We reviewed a prospectively collected and maintained database to identify all patients who underwent a total joint replacement from April 2016 to September 2017. Patients were identified based on DRG codes for primary arthritis of a lower extremity joint, then specifically for foot and ankle, as well as CPT codes for ankle arthroplasty (27702) or ankle arthrodesis (27870/28725). Functional outcomes were assessed based on insurance type. The cohorts were matched for age, comorbidities, and gender. Statistical analysis was performed using chi-squared and paired t-test to assess for differences in patient reported outcomes. Descriptive statistical analysis was used to assess for differences in cost between the cohorts. Results: A total of 573 patients were included.There were 48 replacements and 47 fusions. Arthrodesis procedures costs approximately 6, 500 less per case than the system costs for patients who underwent arthroplasty procedures. The average length of stay for patients who underwent total ankle arthroplasty was 1.6 days compared to outpatient surgical centers utilized for most arthrodesis patients. Overall, patients reported improved pain and a 30.96 increase in FAAM scores. Most patients had a global rate of change that was "very much better" or "much better" (68%). Based on insurance type, patients who underwent a total ankle replacement in the CJR program had improved outcomes and lower cost than patients commercially insured. Conclusion: With the CJR, there is greater emphasis on the optimal intervention for elective operations. There should be coordinated efforts to optimize quality care, while minimizing financial waste within the healthcare system. The price differential suggests an annual potential for financial savings as high as 325, 000 for a system that supports intervention for 50 cases per year. As such, these results suggest that arthroplasty may be optimal for patients with severe symptomatic ankle arthritis, while most patients have adequate relief with an ankle fusion. More importantly, quality improvement efforts should focus on the impact of surgical intervention on functional activity.